Primary failure of eruption (PFE) - a systematic literature review - Hubert Nieścior; Dominika Sereda; Aleksandra Metelska; Jakub Metelski; Monika Szwed (Kazimierz Wielki University, 2022)
Introduction and purpose Primary Failure of Eruption (PFE) is a rare disease that occurs more often in women than in men. PFE is extremely important for orthodontists because conventional treatment of patients results in ankylosis of the teeth affected by the disease. The aim of the study is to discuss the epidemiology, etiology, diagnosis and treatment of Primary Failure of Eruption. Description of the state of knowledge PFE is present in 0.05% to 0.6% of the population. The average incidence is at the age of 13.65, more often in women. Most often it affects the lateral teeth, and therefore it results in open lateral bites because the teeth do not reach the occlusal plane. The condition was found to be of genetic origin and inherited autosomal dominantly with a low percentage of incomplete penetration. The gene responsible for the disease is the PTH1R. The diagnosis of the disease consists in excluding other causes of eruption failure, detecting disease in which such symptoms occur, and genetic tests (NGS). Treatment of an open lateral bite cannot be carried out in a conventional manner due to the deterioration of the condition after the application of orthodontic forces. The result of the above actions is ankylosis of teeth covered by PFE. The currently proposed methods of treatment are: single or multi-site osteotomy, selective extractions with subsequent implantations, direct or indirect composite restorations, distraction osteogenesis, removable prosthetic restorations. Summary Properly conducted clinical examination of the patient should take into account PFE. Genetic testing (PTH1R) is important in the diagnosis of people with eruption disorders, which is crucial for achieving partially positive treatment results. Orthodontic treatment is contraindicated and patients with a PTH1R mutation should be monitored long-term until their growth is complete, which is the time when interdisciplinary treatment is initiated.